Exploring the anti-inflammatory effect of Fructus Gleditsia sinensis Lam., Fructus Gleditsiae abnormalis, and Gymnocladus chinensis Baill. using SPME-GC-MS, network pharmacology, and molecular docking - Qin Ding; Xiang-Pei Wang; Feng Xu; Mei Zhang; Rong-Zhe Fang; Ping Qin; Hong-Mei Wu (Arabian Journal of Chemistry, 2022)
Fructus Gleditsia sinensis Lam. (FGSL), Fructus Gleditsiae abnormalis (FGA), and Gymnocladus chinensis Baill. (GCB) are fruits of leguminous plants that are used in traditional medicine. Among them, FGSL and FGA are developed to different degrees, and GCB is related to them. The literature records indicate their use in the external treatment of carbuncle. Modern pharmacological studies have shown that the formation of a carbuncle is closely related to the occurrence and development of inflammation, and the volatile components contained in the FGSL/FGA drugs have significant anti-inflammatory effects. The solid phase micro extraction-gas chromatography-mass spectrometry (SPME–GC–MS) method was used to analyze the volatile components contained in FGSL, FGA, and GCB. Moreover, the molecular mechanism underlying the anti-inflammatory effects was explored based on network pharmacology and molecular docking. The SPME-GC-MS demonstrated significant differences in the chemical constituents and percentage contents among FGSL, FGA, and GCB. 13 common volatile components were identified in FGSL, FGA, and GCB. Through network pharmacology and molecular docking, the differences in the anti-inflammatory mechanism of FGSL, FGA, and GCB were initially revealed. This study laid the foundation for further study of FGSL, FGA, and GCB. Simultaneously, it also provided a reference for the correct use of FGSL, FGA, and GCB in the clinic.